TINGKAT TRANSPARANSI PENGELOLAAN KEUANGAN DANA DESA DI DESA KEBO KECAMATAN LILIRILAU KABUPATEN SOPPENG - Ratih Purwati Tahir; Andi Syadaruddin; Muhtar Muhtar (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
Qualitative research was used in this study, aiming to describe and describe events and phenomena that occurred in Kebo Village, Lilirilau District, Soppeng Regency, including transparency in the planning, implementation, and supervision of Village Fund Budget (ADD) financial management. The results of the study indicate that the village government is committed to implementing accountable and regulatory-compliant governance. The implementation of transparency not only increases public trust but also strengthens the effectiveness of the financial planning process that is responsive to village needs. The Kebo Village Government has complied with laws and regulations when conducting accountability reports. Compliance with regulations indicates that the village government has implemented the final measure of transparency, namely a legal system that guarantees openness in financial management.